Pelatihan Seni Musik sebagai Media Penguatan Nilai-Nilai Kewarganegaraan bagi Guru dan Siswa Sekolah Dasar - Ridwan Ardi (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
Civic values ​​such as mutual cooperation, tolerance, discipline, and love of the homeland need to be instilled from an early age through a contextual and enjoyable approach. One effective approach is through musical arts that are universal and easily accepted by children. This community service program aims to provide musical arts training to elementary school teachers and students as a learning medium that can strengthen civic values. This activity was carried out at SD Negeri 1 Mawasangka, Central Buton Regency, involving 1 teacher and 30 students in grades IV and V. The training methods included workshops, practicing creating national-themed songs, and collaborative music performances between teachers and students. The results of the activity showed an increase in teachers' understanding of the integration of musical arts in PPKn learning as well as an increase in students' active participation in expressing civic values ​​through music. The songs created by students contain messages of unity, love for the environment, and tolerance that show a good understanding of civic material. This activity also succeeded in building emotional closeness between teachers and students through creative interactions. Thus, this training can be a model for strengthening civic character based on art that is applicable and relevant to elementary education. It is expected that this program can be replicated in other schools as a form of character education innovation through a local arts and culture approach.